Geographic disparities in performance of pediatric polysomnography to diagnose obstructive sleep apnea in a universal access health care system. (August 2021) - Radhakrishnan, D.; Knight, B.; Gozdyra, P.; Katz, S.L.; Maclusky, I.B.; Murto, K.; To, T.M.
Abstract: Background: Diagnostic polysomnography (PSG) is recommended prior to adenotonsillectomy (AT) for children with obstructive sleep apnea (OSA) and certain high-risk characteristics, but resource limitations often prevent this practice. Objective: We performed a population-based assessment of children across Ontario, Canada to describe and quantify disparities in PSG. Methods and materials: This retrospective cohort study was performed using provincial health administrative data held at ICES. We identified children 0–10 years old who underwent PSG and AT between 2009 and 2018, and those with a PSG within 18 months prior to and/or 12 months following AT. We calculated the odds of PSG prior to/following AT after adjustment for demographics, medical comorbidities, geographic and socioeconomic characteristics. Our main predictor was driving time/distance to the nearest pediatric sleep centre ascertained using spatial analysis and geographic information systems. Results: We identified 27, 837 children <10 years old who underwent AT for OSA in Ontario. Only 12.8% had a PSG within 18 months prior and 5.7% had a PSG within 12 months following AT. Shorter driving time/distance, older age, male sex and certain comorbidities were associated with increased odds of PSG. Conclusion: Only a small proportion of children in our cohort underwent PSG prior to or following AT surgery despite universal access to healthcare. This study suggests a need to increase overall PSG access, particularly for those living distant from existing pediatric sleep centres. Future studies could determine if increased PSG testing in 'underserviced areas' would reduce overall surgery rates and/or improve health outcomes. Highlights: Few children in Ontario, Canada undergo polysomnography to confirm obstructive sleep apnea prior to adenotonsillectomy. Pre-operative polysomnography is more likely in patients who live closer to a specialized pediatric sleep centre. Longer driving times to specialized sleep centres reduces polysomnography rates despite risk factors for complications.